2011
DOI: 10.1016/j.yexmp.2011.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of cytokine signaling-3 and intimal hyperplasia in porcine coronary arteries following coronary intervention

Abstract: Aims The growth and differentiation of cells is regulated by cytokines by binding to cell-surface receptors and activating intracellular signal transduction cascade. Suppressor of cytokine signaling (SOCS)-3 is a negative regulator of cytokines. In this study we examined the expression of SOCS3 in porcine coronary artery smooth muscle cells (PCASMCs) in vitro and in proliferating smooth muscle cells of neointimal lesions after coronary artery intervention in a swine model. Methods and Results PCASMCs were cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 33 publications
5
29
0
Order By: Relevance
“…However, the most intriguing and novel finding is that the stimulation of hCASMCs simultaneously with TNF-␣ and IGF-1 significantly decreases the SOCS3 mRNA and protein expression. This supports our recent report in a porcine model (11). However, the underlying molecular mechanisms are unclear.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the most intriguing and novel finding is that the stimulation of hCASMCs simultaneously with TNF-␣ and IGF-1 significantly decreases the SOCS3 mRNA and protein expression. This supports our recent report in a porcine model (11). However, the underlying molecular mechanisms are unclear.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, we reported a significant reduction in the SOCS3 expression in the neointimal lesion after balloon angioplasty in coronary arteries of atherosclerotic swine (11). These neointimal lesions are also highly positive to both TNF-␣ and IGF-1.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…The porcine coronary and rabbit iliac artery models were used, with agents administered systemically or locally. 21 Coronary stents were developed to overcome acute closure and acute recoil. Charles Dotter introduced the concept of stenting by placing the first ''coil spring graft'' in the femoral artery of a dog.…”
Section: History Of Animals In Stent Developmentmentioning
confidence: 99%
“…Suppressor of cytokine signalling-3 (SOCS3) protein decreases the JAK/STAT signalling by blocking the JAK tyrosine kinase activity and the activation of STAT factors, suggesting that it is a novel antineointimal hyperplasia target. Recently, our laboratory has found a significant reduction in SOCS3 expression in the neointimal lesion after balloon angioplasty in coronary arteries of atherosclerotic swine (52). In addition, our laboratory demonstrated that hypermethylation of the SOCS3 gene in SMCs could be an underlying mechanism of intimal hyperplasia and restenosis, suggesting that inhibition of SOCS3 promoter methylation is a potential anti-neointimal hyperplasia target (53).…”
Section: Antineointimal Hyperplasiamentioning
confidence: 77%